Bebida fermentada de umbu (Spondias tuberosa Arruda Câmara) com potencial probiótico utilizando cultura de kefir - Santos, Paula Tais Maia (2022)
The fermented beverage market has been growing approximately 10% per year. This is due to the search for ready-to-eat foods that guarantee nutrition to consumers, especially those with functional properties. Umbu is a tasty and nutritious fruit, with high levels of antioxidant compounds, alkaloids, tannins and flavonoids. When it comes to beneficial components for health, there are also probiotics from fermentation processes that result in substances and microorganisms that provide metabolic and physiological advantages to consumers. Kefir culture has gained prominence in recent years due to its ability to produce various lactic acid microorganisms surrounded by a polysaccharide matrix. The species of microorganisms produced in the kefir culture vary according to the matrix used as the culture medium. Thus, this work aimed to develop an umbu-based kefir drink with probiotic potential. In order to accomplish this, the study defined the matrix to be used for the growth of microorganisms, based on the bioactive compounds, evaluating the combination of 5 umbu pulp concentrations (0%, 35%, 50%, 85% and 100%) and 5 sugar concentrations (4.0%, 5.16%, 8.0%, 10.84% and 12.0%), following the central rotational composite design (CRCD). The optimized formulation underwent sensory analysis, along with other formulations that obtained the highest levels of bioactive compounds. The formulation chosen after the sensory analysis was composed of 50% pulp and 12% sugar. This formulation was then subjected to the analyses of the viability of probiotic microorganisms, as well as bioactive compounds and physicochemical quality. The population of probiotic microorganisms of lactic acid bacteria present remained unchanged (p<0.05) for 28 days of storage at 8°C ± 1°C, with values ranging from 6.58 to 6.93 log CFU/ml. However, acetic bacteria had a significant increase (p<0.05) in the last three days of storage, with population ranging from 7.04 to 7.74 log CFU/ml and yeasts with significant variation (p<0.05 ) in the last two days, with a population between 7.04 and 7.49 log CFU/ml. The phenolic compounds had higher levels from the first to the second week and remained constant up to 21 days at 8°C ± 1°C. Flavonoids showed an increase in concentration up to 21 days at 8°C ± 1°C. There was a degradation of carotenoids during storage. The umbu drink fermented with kefir grains showed satisfactory results during storage, indicating that it is a food with probiotic potential and bioactive compounds.